2021
DOI: 10.1371/journal.pone.0249221
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fatty Liver Index to predict reversion to normoglycemia in people with prediabetes

Abstract: Background Fatty Liver Index (FLI) is strongly associated with changes in glycemic status and incident Type 2 Diabetes (T2D). The probability of reverting to normoglycemia from a state prediabetes could be determined by FLI, however such relationship remains poorly understood. Aim To determine the clinical interest of using FLI to estimate prediabetes reversion at 5 years in patients with impaired fasting plasma glucose at baseline, and identify those factors associated with changes in FLI, that could contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The study also reported that FLI could predict the risk of progressing to T2D as well as the possibility of reverting to normoglycaemia in clinical practice, independently of classical glucose parameters. 46 Moreover, normalisation of glycaemia was higher in subjects with FLI<30 than in those with higher FLI scores. The incidence of T2D observed in our study was higher than in previous ones [47][48][49] probably due to differences in sociodemographic characteristics between study populations.…”
Section: Discussionmentioning
confidence: 94%
“…The study also reported that FLI could predict the risk of progressing to T2D as well as the possibility of reverting to normoglycaemia in clinical practice, independently of classical glucose parameters. 46 Moreover, normalisation of glycaemia was higher in subjects with FLI<30 than in those with higher FLI scores. The incidence of T2D observed in our study was higher than in previous ones [47][48][49] probably due to differences in sociodemographic characteristics between study populations.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, similar conclusions were reached in an open-label, cluster-randomized trial (DiRECT) [ 40 ]. In a 5-year observational cohort study, Busquets-Cortés et al [ 41 ] included a total of 16,648 adults with prediabetes. This study further demonstrated that regular physical activity and a healthy diet can help reverse prediabetes by improving the degree of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this was not only the difference in dosage; the progression of diabetes could also weaken the effect of long-term intervention over time. Prediabetes is a reversible process, but T2DM is not [52]. Therefore, the longer the vitamin D supplementation in prediabetes, the more effective the prevention of the onset of diabetes and the less likely the disease will progress.…”
Section: Discussionmentioning
confidence: 99%